2014
DOI: 10.1098/rspb.2013.2641
|View full text |Cite
|
Sign up to set email alerts
|

Fish introductions reveal the temperature dependence of species interactions

Abstract: A major area of current research is to understand how climate change will impact species interactions and ultimately biodiversity. A variety of environmental conditions are rapidly changing owing to climate warming, and these conditions often affect both the strength and outcome of species interactions. We used fish distributions and replicated fish introductions to investigate environmental conditions influencing the coexistence of two fishes in Swedish lakes: brown trout (Salmo trutta) and pike (Esox lucius)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
91
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(98 citation statements)
references
References 43 publications
6
91
0
1
Order By: Relevance
“…small lakes (1 ha) up to þ38C for larger lakes (100 ha). Thus, the predicted warming is expected to cause dramatic shifts in the composition of the species-poor communities of lakes in northern Scandinavia, with hitherto unstudied consequences for ecosystem function [32][33][34]. Given the potential importance of thresholds in the temperature response of consumption rates, it becomes important to ask under what conditions we should expect to see them and how common they are.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…small lakes (1 ha) up to þ38C for larger lakes (100 ha). Thus, the predicted warming is expected to cause dramatic shifts in the composition of the species-poor communities of lakes in northern Scandinavia, with hitherto unstudied consequences for ecosystem function [32][33][34]. Given the potential importance of thresholds in the temperature response of consumption rates, it becomes important to ask under what conditions we should expect to see them and how common they are.…”
Section: Discussionmentioning
confidence: 99%
“…The threshold in the temperature dependence of attack rate that we observed in this study has an intriguing correspondence with observed patterns of coexistence between pike and brown trout in northern Scandinavia. The two species coexist in small cold lakes, but not in small warm lakes, where northern pike cause the extinction of brown trout [32]. The critical annual mean air temperature, that appears to form a tipping point, varies from þ18C for Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…For observations in which latitude and longitude were available, we extracted bioclimatic data on seasonality in thermal conditions (see the electronic supplementary material, figure S2 for map of localities). Seasonality for terrestrial and freshwater taxa was the standard deviation of annual mean weekly air temperatures extracted from 0.25 Â 0.25 0 Bioclim climatic layers (Bioclim variable Bio4; air temperature is often used as a proxy for freshwater thermal conditions [45]). Seasonality for marine taxa was the standard deviation of mean weekly Sea Surface Temperatures from 1989 to 2014, taken from NOAAs 18 Â 18 Optimum Interpolated Sea Surface Temperature dataset.…”
Section: Methodsmentioning
confidence: 99%
“…The spread of warm-adapted fish species upstream and to northern latitudes often results in local extinctions of cold-adapted salmonid species (Hein et al 2014). Barriers such as waterfalls, dams and weirs can limit the upstream spread of such novel colonizers, thereby creating refuges for threatened native species.…”
mentioning
confidence: 99%